Respiratory morbidity through the first decade of life in a national cohort of children born extremely preterm - Kaia Skromme; Maria Vollsæter; Knut Øymar; Trond Markestad; Thomas Halvorsen (BMC, 2018)
Abstract Background Advances in perinatal care have markedly increased the prospects of survival for infants born extremely preterm (EP). The aim of this study was to investigate hospitalisation rates and respiratory morbidity from five to 11 years of age in a prospective national cohort of EP children born in the surfactant era. Methods This was a national prospective cohort study of all children born in Norway during 1999 and 2000 with gestational age (GA) < 28 weeks or birth weight < 1000 grams, and of individually matched term-born controls recruited for a regional subsample. Data on hospital admissions, respiratory symptoms, and use of asthma medication was obtained by parental questionnaires at 11 years of age. Results Questionnaires were returned for 232/372 (62%) EP-born and 57/61 (93%) regional term-born controls. Throughout the study period, 67 (29%) EP-born and seven (13%) term-born controls were admitted to hospital (odds ratio (OR) 2.90, 95% confidence interval (CI): 1.25, 6.72). Admissions were mainly due to surgical procedures, with only 12% due to respiratory causes, and were not influenced by neonatal bronchopulmonary dysplasia (BPD) or low GA(≤ 25 weeks). Respiratory symptoms, asthma and use of asthma medication tended to be more common for EP-born, significantly so for medication use and wheeze on exercise. Neonatal BPD was a risk factor for medication use, but not for current wheeze. In multivariate regression models, home oxygen after discharge (OR 4.84, 95% CI: 1.38, 17.06) and parental asthma (OR 4.38, 95% CI: 1.69, 11.38) predicted current asthma, but neither BPD nor low GA were associated with respiratory symptoms at 11 years of age. Conclusions Hospitalisation rates five to 11 years after EP birth were low, but twice those of term-born controls, and unrelated to neonatal BPD and low GA. Respiratory causes were rare. Respiratory complaints were more common in children born EP, but the burden of symptoms had declined since early childhood.